Biological Evaluation of Polyvinyl Alcohol Hydrogels Enriched by Hyaluronic Acid and Hydroxyapatite - Chocholata, Petra; Kulda, Vlastimil; Dvorakova, Jana; Kolaja Dobra, Jana; Babuska, Vaclav (International journal of molecular sciences, 2020)
This study aimed to develop polyvinyl alcohol (PVA) -based scaffold enriched with hyaluronic acid (HA) and hydroxyapatite (HAp) using physical crosslinking by freezing-thawing method. We accomplished biological evaluation of scaffolds, swelling degree, bioactivity assessment, and hemolytic test. The results showed that all types of scaffolds should be safe for use in the human body. The culturing of human osteoblast-like cells MG-63 and their proliferation showed better adhesion of cells due to the presence of HA and confirmed better proliferation depending on the amount of HAp. This paper gives the optimal composition of the scaffold and the optimal amount of the particular components of the scaffold. Based on our results we concluded that the best PVA/HA/HAp combination is in the ratio 3:1:2.
Keywords: proliferace buněk; tkáňové podpůrné struktury; Cell Line, Tumor; biokompatibilní materiály; osteoblasty; buněčná adheze; Polyvinyl Alcohol; lidé; tkáňové inženýrství; Hydrogels; Cell Adhesion; kyselina hyaluronová; polyvinylalkohol; Hyaluronic Acid; Durapatite; Biocompatible Materials; Materials Testing; Osteoblasts; hydrogely; Cell Proliferation; testování materiálů; Tissue Engineering; Cell Survival; viabilita buněk; Tissue Scaffolds; hydroxyapatit; nádorové buněčné linie; Humans